سلطة القاضي في إسناد الحضانة في القانون الجزائري - سهام خضار - عائشة قويدري (جامعة المسيلة, 2024)
موضوع سلطة القاضي في إسناد الحضانة له أهميته النابعة من الفئة التي أراد الفقه الإسلامي والمشرع الجزائري حمايتها، ومن الحضانة ذاتها فهي آلية لا غنى عنها في توفير حاجيات الصغير وتنشئته، وإن هدفنا من هذا البحث يكمن في تسليط الضوء على الممارسة العملية للقاضي عند إسناده الحضانة وموازنته بين تطبيق نصوص قانون الأسرة ومراعاة مصلحة المحضون التي جعلها المشرع الجزائر الأساس في إسناد الحضانة، وبيان الحلول التي اعتمدها القضاء الجزائري في حالة غموض أو سكوت المشرع عن تنظيم مسألة تتعلق بالمحضون، واعتمدنا في ذلك على المنهج المقارن والوصفي. وقد توصلنا إلى مجموعة من النتائج من أبرزها: أنّ مدار الحضانة مراعاة مصلحة المحضون فحيثما وجدت وجب على القاضي مراعاتها، سواء في ترتيب الحاضنين عند إسنادها أو عند إعادتها لمن أسقطت عنه أو لمن تنازل عنها، مع ذلك هناك بعض المسائل أغفلها المشرع رغم أهميتها منها؛ المتعلقة بتفصيل شروط الحضانة، وكذا عدم تحديده للأقربون درجة الوارد في المادة 64 ق أج، ومما نقترحه ضبط مصطلح مصلحة المحضون لأنه فضفاض ويخضع للسلطة التقديرية الواسعة للقاضي، وإعادة صياغة المادة 64 ق أ ج بإعطاء الأولوية للأقربون من النساء لأنهن الأكثر صبرا وتحملا لأعباء الحضانة. الكلمات المفتاحية: الحضانة، السلطة التقديرية، القاضي، المحضون الملخص باللغة الانجليزية The issue of the judge's authority in assigning custody has its importance stemming from the category that Islamic jurisprudence and the Algerian legislator wanted to protect, and from custody itself, it is an indispensable mechanism in providing the needs of the child and his upbringing, and our goal from this research lies in highlighting the practical practice of the judge when assigning custody and balancing between the application of the provisions of the family law and taking into account the interest of the custodians, which the Algerian legislator has made the basis for assigning custody, and Comparative and descriptive approach. الملخص We have come to a set of conclusions, the most prominent of which are: that the custody must take into account the interests of the custodians, wherever they exist, the judge must take them into account, whether in the order of the custodians when assigning it or when returning it to the one who dropped it or to the one who relinquished it, however, there are some issues overlooked by the legislator, despite their importance; related to the detail of the conditions of custody, as well as his failure to specify the degree of relatives contained in Article 64 S. A. C., and from what we propose to adjust the term of custody interest because it is loose and subject to the broad discretion of the judge, and reformulating Article 64 S. A. C by giving priority to the closest women because they are the most patient and bear the burdens of custody. Keywords: Custody, Discretion, Judge, Custodians
Keywords: الكلمات المفتاحية: الحضانة،